Moving carbon between spheres, the potential oxalate-carbonate pathway of Brosimum alicastrum Sw.; Moraceae - Rowley, Mike C.; Estrada-Medina, Héctor; Tzec-Gamboa, Magnolia; Rozin, Aviram; Cailleau, Guillaume; Verrecchia, Eric P.; Green, Iain (Plant and soil, 2017)
Aims: The Oxalate-Carbonate Pathway (OCP) is a biogeochemical process that transfers atmospheric CO₂ into the geologic reservoir as CaCO₃; however, until now all investigations on this process have focused on species with limited food benefits. This study evaluates a potential OCP associated with Brosimum alicastrum, a Neotropical species with agroforestry potential (ca. 70-200 kg-nuts yr⁻¹), in the calcareous soils of Haiti and Mexico. Methods / results: Enzymatic analysis demonstrated significant concentrations of calcium oxalate (5.97 % D.W.) were associated with B. alicastrum tissue in all sample sites. The presence of oxalotrophism was also confirmed with microbiological analyses in both countries. High concentrations of total calcium (>7 g kg⁻¹) and lithogenic carbonate obscured the localised alkalinisation and identification of secondary carbonate associated with the OCP at most sample sites, except Ma Rouge, Haiti. Soils adjacent to subjects in Ma Rouge demonstrated an increase in pH (0.63) and CaCO₃ concentration (5.9 %) that, when coupled with root-like secondary carbonate deposits in Mexico, implies that the OCP does also occur in calcareous soils. Conclusions: Therefore this study confirms that the OCP also occurs in calcareous soils, adjacent to B. alicastrum, and could play a fundamental and un-accounted role in the global calcium-carbon coupled cycle.